Diseño de un modelo genérico de análisis de clusters a partir del cálculo de factores pertinentes a la metodología sandag (2018)
In this work, it was developed based on the SANDAG methodology, since by means of a data panel type statistical analysis it was possible to establish the evolution of the variables in the course of time analyzed, in order to identify the preconditions of technological capabilities and of manufacturing to determine the potential for development and innovation. The most influential factor for the analysis was the Employment Concentration Factor, because the proportion of employment with added value (professional, masters and doctorate) is evaluated with respect to the national level, in order to identify the capacity to innovate in productive processes that allow to generate competitive advantages, grow and generate higher productivity and employment, having a high influence on the generation of wealth and prosperity in the region, which will be measured with the Economic Prosperity Factor through the relationship of the Internal Product Gross (GDP), and the number of workers of the companies that were the object of study and by means of the Cluster Dependency Factor, which is determined through the linkages the importance of the sector in the national economy.